Cholesterol Metabolism in T Cells - Bietz, Andreas; Zhu, Hengyu; Xue, Manman; Xu, Chenqi (Frontiers in Immunology, 2017)
Compartmentalization is arguably one of the first critical criteria for the existence of cell-based life. All reactions in cells rely on spatial control of their components, as well as long term storage of encoded information. The lipid bilayer and its associated organelles form the foundation for all reactions and structures in the cell. Sterols (mainly cholesterol in mammalian cells), phospholipids, sphingolipids, and proteins form an integral part in maintaining optimal stability and fluidity of the membrane. In this review, cholesterol metabolism will be examined in general. Further, the importance of the cholesterol pathway in activation and function of T cells as well as the methods to modulate this pathway in disease contexts will be discussed.